(untitled) (Homoeopathy for All, 2026)
The term “Varicose Veins” originates from the Latin word “varix”, meaning “twisted It represents a common form of venous disease, characterized by swollen, engorged blood vessels that bulge under the skin’s surface. These Veins typically appear blue or purple in colour, resembling like cords running just beneath the surface of your skin.